Operation fix Marabelle - Parent, Nancy (New York, NY Harper, an imprint of HarperCollins Publishers, 2020)
Fancy Nancy discovers a new talent for repairing broken toys in her neighborhood, but she must learn to keep her cool when her next patient is her beloved doll Marabelle.
Guided reading level